Design and Analysis of an ESP-NOW-Based Handover Mechanism in a Multi-Node ESP32 Peer-to-Peer Network for River Water Level Monitoring Systems in Areas Without Internet Connectivity - Randy Prandana; Berkat Iman Telaumbanua; Felix Al Vincentz (Universitas Mahkota Tricom Unggul, 2026)
River water level monitoring systems in remote areas face significant challenges due to the limited availability of internet network infrastructure. This study designs and analyzes a handover mechanism based on the ESP-NOW protocol utilizing peer-to-peer (P2P) communication among ESP32 nodes as a solution for a standalone monitoring system without dependency on routers or internet connectivity. The proposed architecture consists of multiple ultrasonic sensor nodes that communicate directly through ESP-NOW and are equipped with a dynamic handover algorithm based on Received Signal Strength Indicator (RSSI) values to ensure continuous data transmission during communication disruptions or network topology changes. Experimental evaluations were conducted under field scenarios with varying distances ranging from 10 to 200 meters, environmental obstacles, and simultaneous active node switching conditions. The performance metrics assessed include handover latency, packet loss rate, throughput, and power consumption. The experimental results demonstrate that the proposed handover mechanism successfully maintains network connectivity with an average latency below 50 ms and a packet loss rate of less than 3% under normal operating conditions. The findings indicate that ESP-NOW can be effectively implemented as a reliable communication protocol for flood early warning systems in areas lacking internet infrastructure, offering low implementation costs and minimal power consumption.